2019
DOI: 10.1111/cup.13466
|View full text |Cite
|
Sign up to set email alerts
|

Refractory macrophage activation syndrome in the setting of adult‐onset Still disease with hemophagocytic lymphohistiocytosis detected on skin biopsy treated with canakinumab and tacrolimus

Abstract: A 19-year-old Caucasian female with adult-onset Still disease (AOSD) presented for evaluation of an acute clinical decompensation and atypical annular papules and plaques with purpura on the lower extremities. A punch biopsy demonstrated histiocytes with engulfed degenerated erythrocytes and lymphocytes, consistent with hemophagocytic lymphohistiocytosis (HLH). HLH, clinically referred to as macrophage activation syndrome, is a rare complication of AOSD and is life-threatening.Relevant clinical, laboratory, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…However, other authors described polymorphous cutaneous lesions or atypical cutaneous presentations as erythematous or brown eruptions, 59 less commonly violaceous in colour, 59 linear configurations simulating dermographism 60 or flagellate dermatitis, prurigo‐pigmentosa‐like, 59 urticarial papules, 60 dermatomyositis‐like 59 and lichen amyloidosis‐like eruptions 59 . Chamseddin et al 61 reported a 19‐year‐old woman who developed acute clinical decompensation and atypical annular papules and plaques with purpura on the down extremities. A punch biopsy demonstrated histiocytes with engulfed degenerated erythrocytes and lymphocytes, consistent with hemophagocytic lymphohistiocytosis (HLH).…”
Section: Skin Conditions Related To Hypercoagulability That Show Histmentioning
confidence: 99%
See 4 more Smart Citations
“…However, other authors described polymorphous cutaneous lesions or atypical cutaneous presentations as erythematous or brown eruptions, 59 less commonly violaceous in colour, 59 linear configurations simulating dermographism 60 or flagellate dermatitis, prurigo‐pigmentosa‐like, 59 urticarial papules, 60 dermatomyositis‐like 59 and lichen amyloidosis‐like eruptions 59 . Chamseddin et al 61 reported a 19‐year‐old woman who developed acute clinical decompensation and atypical annular papules and plaques with purpura on the down extremities. A punch biopsy demonstrated histiocytes with engulfed degenerated erythrocytes and lymphocytes, consistent with hemophagocytic lymphohistiocytosis (HLH).…”
Section: Skin Conditions Related To Hypercoagulability That Show Histmentioning
confidence: 99%
“…A punch biopsy demonstrated histiocytes with engulfed degenerated erythrocytes and lymphocytes, consistent with hemophagocytic lymphohistiocytosis (HLH). MAS, a variant of secondary HLH occurring in the setting of autoimmune disease, is a life‐threatening condition with reported mortality rate of 20% to 50% 61 . It has been reported in 3% to 20% of AOSD cases 61 .…”
Section: Skin Conditions Related To Hypercoagulability That Show Histmentioning
confidence: 99%
See 3 more Smart Citations